Novel ZnO-binding peptides obtained by the screening of a phage display peptide library - Golec, Piotr (Springer Netherlands, 2012)
Zinc oxide (ZnO) is a semiconductor compound with a potential for wide use in various applications, including biomaterials and biosensors, particularly as nanoparticles (the size range of ZnO nanoparticles is from 2 to 100 nm, with an average of about 35 nm). Here, we report isolation of novel ZnO-binding peptides, by screening of a phage display library. Interestingly, amino acid sequences of the ZnO-binding peptides reported in this paper and those described previously are significantly different. This suggests that there is a high variability in sequences of peptides which can bind particular inorganic molecules, indicating that different approaches may lead to discovery of different peptides of generally the same activity (e.g., binding of ZnO) but having various detailed properties, perhaps crucial under specific conditions of different applications.